Transparent composite material for displaying luminescence and preparation method and application thereof

A transparent composite material with a polycarbonate-based luminescent layer and ceramic-doped polymer anti-slip, wear-resistant layer addresses inflexibility and safety issues in road traffic pavement displays, offering multi-angle luminescence and improved durability.

CN119193016APending Publication Date: 2024-12-27SHANGHAI SANSI ELECTRONICS ENG +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317186.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Current road traffic pavement displays using road marking paint are inflexible and pose safety hazards due to specular reflection from tempered glass, leading to potential vehicle slips and reduced visibility in low-brightness conditions.

Method used

A transparent composite material comprising a polycarbonate-based luminescent layer with azo, hydrazine, or azole compounds for chemical pore formation and a ceramic-doped polymer anti-slip, wear-resistant layer for improved light transmission, anti-slip, and wear resistance.

Benefits of technology

The composite material provides multi-angle luminescence, enhanced visibility, anti-slip properties, and increased durability, addressing the limitations of passive luminescence and safety hazards in road traffic pavement displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193016A_ABST
    Figure CN119193016A_ABST
Patent Text Reader

Abstract

The invention relates to the field of road traffic pavement display, in particular to a transparent composite material for display luminescence and a preparation method and application thereof. The transparent composite material comprises a basic transparent luminous layer and an anti-skid wear-resistant layer, the raw materials of the basic transparent light-emitting layer comprise polycarbonate and azo, hydrazine or azole compounds, and the raw materials of the anti-skid wear-resistant layer comprise aluminum oxide and epoxy / acrylic resin. According to the composite material, a high-performance polymer composite material is mainly adopted, and a unique chemical pore-forming technology is utilized, so that the capabilities of pressure resistance, weather resistance and multi-angle light emitting are achieved; and the ceramic-doped high-molecular anti-slip wear-resistant layer is implanted into the outer surface of the composite material, so that the light-transmitting, anti-slip and wear-resistant effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road traffic pavement display, and in particular to a transparent composite material for displaying luminescence, and a preparation method and application thereof. Background Art

[0002] Currently, road traffic pavement ground displays mostly use road marking paint for indication and identification, which cannot be changed and adjusted instantly, especially variable lanes and tidal lanes, which need to be flexibly adjusted according to the two-way traffic flow in order to improve vehicle traffic efficiency and alleviate road congestion.

[0003] In order to ensure that the road surface display can also serve as an indicator in low-brightness conditions, a device with a light-emitting function is usually used for auxiliary display. In the prior art, tempered glass is used as the light-emitting layer of the light-emitting device because of its smooth surface and easy specular reflection, which can easily cause the vehicle to slip and cause a safety hazard to the driver. Summary of the invention

[0004] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide a transparent composite material for displaying luminescence, and a preparation method and application thereof. The composite material mainly adopts a high-performance polymer composite material and utilizes a unique chemical pore-making technology to achieve the capabilities of pressure resistance, weather resistance, and multi-angle luminescence; and a ceramic-doped polymer anti-slip and wear-resistant layer is implanted on the outer surface of the composite material to achieve the effects of light transmission, anti-slip, and wear resistance.

[0005] The technical solution of the present invention is:

[0006] In one aspect, the present invention provides a transparent composite material for displaying luminescence, the transparent composite material comprising a basic transparent luminescent layer and an anti-slip and wear-resistant layer; the raw materials of the basic transparent luminescent layer comprise polycarbonate and azo, hydrazine or azole compounds, and the raw materials of the anti-slip and wear-resistant layer comprise aluminum oxide and resin. Preferably, the resin is a modified epoxy resin or acrylic resin.

[0007] A second aspect of the present invention provides a method for preparing a transparent composite material for displaying luminescence, the method comprising the following steps:

[0008] 1) Mixing polycarbonate with azo, hydrazine or azole compounds and then extruding or injection molding to obtain a polycarbonate sheet or three-dimensional structure;

[0009] 2) mixing alumina and resin to obtain a mixed resin composite;

[0010] 3) The mixed resin composite obtained in step 2) is laid flat on the surface of the polycarbonate sheet plate or three-dimensional structure obtained in step 1) for pre-curing and curing to obtain a transparent composite material for displaying luminescence.

[0011] The third aspect of the present invention provides the use of the transparent composite material for displaying luminescence as described in the first aspect of the present invention and / or the transparent composite material for displaying luminescence prepared by the preparation method as described in the second aspect of the present invention in the field of road traffic pavement display.

[0012] By adopting the above technical solution, the beneficial effects of the present invention are:

[0013] The material of the present invention effectively solves the problem that current ground road signs can only adopt passive luminescence schemes. The composite material of the present invention uses polycarbonate as the base material, has the characteristics of high strength, good light transmittance, excellent weather resistance, etc., and uses azo, hydrazine or azole compounds to perform closed-cell chemical pore formation, forming a large number of bubbles inside the polycarbonate substrate, which can refract and reflect the bottom light multiple times, increase the light output angle, and be more conducive to the observation of vehicles in different directions. The surface is rolled into a concave and convex surface, which can increase the bonding area of ​​the later combination with the wear-resistant layer and provide reliability; transparent alumina inorganic material is used as a wear-resistant layer on the surface of polycarbonate to increase the service life of the material; flexible epoxy or acrylic resin is used as an adhesive, which has high bonding strength and excellent impact resistance, and can withstand repeated rolling by vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Shown is a schematic structural diagram of a luminescent transparent composite material according to the present invention. DETAILED DESCRIPTION

[0015] Hereinafter, the transparent composite material for displaying luminescence provided by the present invention and the preparation method and application thereof are described in detail.

[0016] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0017] After a lot of exploration and research, the inventor of the present invention uses polycarbonate as the basic material, which has the characteristics of high strength, good light transmittance, and excellent weather resistance. Azo, hydrazine or azole compounds are used to form closed-cell chemical pores, forming a large number of bubbles inside the polycarbonate substrate, which can refract and reflect the bottom light multiple times, increase the light output angle, and be more conducive to the observation of vehicles in different directions. The surface is rolled into a concave and convex surface to increase the bonding area of ​​the later combination with the wear-resistant layer, providing reliability; transparent alumina inorganic material is used on the surface of polycarbonate as a wear-resistant layer to increase the service life of the material; flexible epoxy or acrylic resin is used as an adhesive, which has high bonding strength and excellent impact resistance, and can withstand repeated rolling of vehicles. On this basis, this application is completed.

[0018]

Transparent composite materials for displaying luminescence

[0019] The present invention provides a transparent composite material for displaying luminescence, wherein the transparent composite material comprises a basic transparent luminescent layer and an anti-slip and wear-resistant layer; the raw materials of the basic transparent luminescent layer comprise polycarbonate and azo, hydrazine or azole compounds, and the raw materials of the anti-slip and wear-resistant layer comprise aluminum oxide and resin.

[0020] In the transparent composite material for displaying luminescence provided by the present invention, the mass ratio of the polycarbonate to the azo, hydrazine or azole compound is 100:(1-5). Optionally, the mass ratio of the polycarbonate to the azo, hydrazine or azole compound can be, for example, 100:(1-2), 100:(2-5), 100:(1-3), 100:(3-5), 100:(1-4), 100:(4-5), 100:(2-3) or 100:(3-4), etc.

[0021] In the transparent composite material for displaying luminescence provided by the present invention, the azo, hydrazine or azole compound is one or more selected from triazole, azobisisobutyronitrile, azodicarbonamide, benzenesulfonylhydrazide and p-toluenesulfonylhydrazide.

[0022] In the transparent composite material for displaying luminescence provided by the present invention, a large number of bubbles are formed inside the polycarbonate substrate by closed-cell chemical pore formation through azo, hydrazine or azole compounds, and optionally, the porosity of the basic transparent luminescent layer accounts for 10% to 50%. Further optionally, the porosity of the basic transparent luminescent layer can be, for example, 10% to 12%, 10% to 15%, 10% to 30%, 15% to 30%, 30% to 50%, 15% to 20%, 20% to 50%, 15% to 35%, 35% to 50%, 15% to 40%, 45% to 50%, 20% to 30% or 30% to 40%, etc. The advantages within the above range are: due to the presence of the pores, it can provide light scattering effect and present multi-angle luminescence, and the pores can shrink under high-intensity pressure to provide toughness support for the composite material. The disadvantage of too high porosity is that the overall strength of the composite material is low and is insufficient to support high-intensity pressure. The disadvantage of too low porosity is poor light scattering effect and inability to present multi-angle luminescence.

[0023] In the transparent composite material for displaying luminescence provided by the present invention, the mass ratio of aluminum oxide to resin is (10-50): (50-90). Optionally, the mass ratio of aluminum oxide to resin is (20-50): (50-80), (30-50): (50-70) or (50-60): (40-50), etc. The advantage of being within the above range is that it can provide the overall wear resistance of the material while maintaining a certain toughness. The disadvantage of being too high is that the composite material has low toughness and is easy to break and crack under high-intensity pressure. The disadvantage of being too low is poor wear resistance.

[0024] In the transparent composite material for displaying luminescence provided by the present invention, the aluminum oxide is transparent aluminum oxide microbeads. The particle size of the aluminum oxide is 2 to 20 microns. Optionally, the particle size of the aluminum oxide can be, for example, 2 to 5 microns, 3 to 5 microns, 5 to 8 microns, 5 to 10 microns, 10 to 15 microns, 10 to 20 microns, etc. Preferably, the surface of the aluminum oxide microbeads is surface modified to improve the affinity of the aluminum oxide microbeads with the resin and improve the uniformity of dispersion. The advantage within the above range is that the aluminum oxide powder is not easy to agglomerate and is not easy to settle in the resin. The disadvantage of too high a particle size is that the aluminum oxide powder is easy to settle and the surface wear resistance of the anti-wear layer is poor. The disadvantage of too low a particle size is that the aluminum oxide powder is easy to agglomerate, which is not conducive to uniform dispersion in the resin.

[0025] In the transparent composite material for displaying luminescence provided by the present invention, the resin is selected from modified epoxy resin or acrylic resin, and the modified epoxy resin or acrylic resin can be, for example, a flexible modified epoxy resin or flexible acrylic resin, and the flexible modified epoxy resin or flexible acrylic resin is specifically modified by grafting with silicone or polyurethane functional groups.

[0026] In the transparent composite material for displaying luminescence provided by the present invention, the thickness ratio of the basic transparent luminous layer to the anti-slip and wear-resistant layer is 100:0.1-0.4, and can be 100:0.1-0.2, 100:0.1-0.3, 100:0.2-0.3 or 100:0.3-0.4. The thickness of the anti-slip and wear-resistant layer is 20 to 200 microns. The advantage of being within the above range is that the coating has high transmittance and moderate anti-slip and wear resistance. The disadvantage of being too high is that the coating is too thick, resulting in reduced transmittance. The disadvantage of being too low is poor anti-slip and wear resistance.

[0027] In the transparent composite material for displaying light provided by the present invention, the contact surface between the basic transparent light-emitting layer and the anti-slip and wear-resistant layer is a frosted or sawtooth structure. The frosted or sawtooth structure is used to increase the surface area and the implantation of the anti-slip and wear-resistant layer.

[0028] In the transparent composite material for displaying light provided by the present invention, the side of the anti-slip and wear-resistant layer away from the basic transparent light-emitting layer is frosted or serrated. For example, before the flexible modified epoxy or acrylic resin is cured, the anti-slip and wear-resistant layer is molded or knurled to achieve a special pattern effect on the surface, thereby achieving anti-slip and wear-resistant effects.

[0029] [Preparation method for transparent composite material for displaying luminescence]

[0030] The present invention also provides a method for preparing a transparent composite material for displaying luminescence, the preparation method comprising the following steps:

[0031] 1) Mixing polycarbonate with azo, hydrazine or azole compounds and then injecting or extruding to obtain a polycarbonate sheet or three-dimensional structure;

[0032] 2) mixing alumina and resin to obtain a mixed resin composite;

[0033] 3) The mixed resin composite obtained in step 2) is laid flat on the surface of the polycarbonate sheet plate or three-dimensional structure obtained in step 1) for pre-curing and curing to obtain a transparent composite material for displaying luminescence.

[0034] In the method for preparing a transparent composite material for displaying luminescence provided by the present invention, step 1) is to mix polycarbonate with an azo, hydrazine or azole compound and then inject or extrude to obtain a polycarbonate sheet. Specifically:

[0035] In step 1) of the present invention, the polycarbonate needs to be dried to obtain the dried polycarbonate, and the dried polycarbonate is mixed with the azo, hydrazine or azole compound. The drying temperature can be, for example, 100 to 120° C., and can be 100 to 110° C. or 110 to 120° C., etc. The drying time can be, for example, more than 4 hours.

[0036] In step 1) of the present invention, the polycarbonate and the azole compound are mixed uniformly.

[0037] In step 1) of the present invention, the specific selection and usage of polycarbonate and azo, hydrazine or azole compounds refer to the description of the luminescent transparent composite material described in the first aspect of the present invention.

[0038] In step 1) of the present invention, injection molding or extrusion is performed in an injection molding machine or an extruder barrel, and the barrel temperature may be, for example, 70 to 100° C., or may be 70 to 90° C. or 90 to 100° C., etc.

[0039] In step 1) of the present invention, the molding temperature is 260° C. to 310° C. Optionally, the molding temperature may be, for example, 260° C. to 280° C., 280° C. to 310° C., 260° C. to 290° C., 290° C. to 310° C., 260° C. to 300° C. or 300° C. to 310° C., etc.

[0040] In the method for preparing a transparent composite material for displaying luminescence provided by the present invention, step 2) is to mix aluminum oxide with a resin to obtain a mixed resin composite, wherein the resin is a flexible epoxy resin or an acrylic resin.

[0041] In step 2) of the present invention, aluminum oxide is uniformly mixed with flexible epoxy or acrylic resin.

[0042] In step 2) of the present invention, the specific selection and dosage of aluminum oxide and flexible epoxy or acrylic resin refer to the description of the luminescent transparent composite material described in the first aspect of the present invention.

[0043] In the method for preparing a transparent composite material for displaying luminescence provided by the present invention, step 3) is to lay the mixed resin obtained in step 2) on the surface of the polycarbonate substrate obtained in step 1) for pre-curing and curing to obtain a transparent composite material for displaying luminescence. Specifically:

[0044] In step 3) of the present invention, the pre-curing temperature is 20°C-80°C. It can be selected from 20°C-30°C, 30°C-80°C, 20°C-40°C, 40°C-80°C, 20°C-50°C, 50°C-80°C, 20°C-60°C, 60°C-80°C, 20°C-70°C, 70°C-80°C, 50°C-60°C, 60°C-70°C or 50°C-70°C.

[0045] In step 3) of the present invention, the pre-curing time is 0.1 to 2 hours, and can be 0.1 to 1 hour or 1 to 2 hours.

[0046] In step 3) of the present invention, the curing temperature is 30°C to 80°C. It can be selected from 30°C to 40°C, 40°C to 80°C, 30°C to 50°C, 50°C to 80°C, 30°C to 60°C, 60°C to 80°C, 30°C to 70°C, 70°C to 80°C, 50°C to 60°C, 60°C to 70°C or 50°C to 70°C.

[0047] In step 3) of the present invention, the curing time is 1 to 6 hours, and can be 1 to 2 hours, 1 to 4 hours, or 4 to 6 hours.

[0048] In step 3), after the pre-curing, a frosted or serrated structure is pressed out, and then the curing is performed. For example, a roller with a pattern is used to press out an uneven pattern on the surface of the pre-cured substrate.

[0049] The transparent composite material for displaying luminescence can be prepared by the aforementioned preparation method of the present invention.

[0050]

use

[0051] The present invention also provides the use of the transparent composite material for displaying luminescence as described above in the present invention and / or the transparent composite material for displaying luminescence prepared by the preparation method as described above in the present invention in the field of road traffic pavement display.

[0052] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.

[0053] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.

[0054] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0055] In the following examples, unless otherwise specified, various raw materials of the present invention can be purchased from the market or prepared according to conventional methods in the art.

[0056] Polycarbonate purchased from Teijin 1250Z

[0057] Flexible modified epoxy resin was purchased from Jinhua JT-3AB.

[0058] Ordinary epoxy resin purchased from Jinhua 612AB-SS

[0059] Example 1

[0060] The steps for composite material molding are as follows:

[0061] Step 1: drying the transparent polycarbonate raw material at 110° C. for more than 4 hours to obtain dried polycarbonate plastic particles;

[0062] Step 2: uniformly mix a mixture of triazole and azodicarbonamide accounting for 2% of the mass of the dried polycarbonate plastic particles with the dried polycarbonate plastic particles; wherein the mass ratio of triazole to azodicarbonamide is 4:6.

[0063] Step 3: Add the mixed raw materials into the barrel of the injection molding machine / extruder, and set the barrel temperature to 80°C;

[0064] Step 4: Set the molding temperature to 270°C, injection / extrude the polycarbonate sheet, and the porosity is about 10%;

[0065] Step 5: Evenly mix 20% by mass of transparent alumina microbeads (particle size 3-5 microns) and 80% of flexible modified epoxy resin;

[0066] Step 6: Evenly spread the mixed resin on the surface of the polycarbonate substrate;

[0067] Step 7: Pre-curing the substrate covered with resin at a curing temperature of 25°C for 2 hours;

[0068] Step 8: Use a roller with a pattern to press out an uneven pattern on the surface of the pre-cured substrate;

[0069] Step 9: Place the embossed substrate at 80°C for 2 hours to cure the resin completely;

[0070] Step 10: After the resin is cured, the molding and processing of the material are completed. The thickness of the basic transparent luminous layer and the anti-slip and wear-resistant layer are 15 mm and 40 μm respectively.

[0071] Example 2

[0072] The steps for composite material molding are as follows:

[0073] Step 1: drying the transparent polycarbonate raw material at 110° C. for more than 4 hours to obtain dried polycarbonate plastic particles;

[0074] Step 2: uniformly mix a mixture of triazole and azodicarbonamide accounting for 5% of the mass of the dried polycarbonate plastic particles with the dried polycarbonate plastic particles; wherein the mass ratio of triazole to azodicarbonamide is 4:6.

[0075] Step 3: Add the mixed raw materials into the barrel of the injection molding machine / extruder, and set the barrel temperature to 80°C;

[0076] Step 4: Set the molding temperature to 270°C, injection / extrude the polycarbonate sheet, and the porosity is about 30%;

[0077] Step 5: Evenly mix 30% by mass of transparent alumina microbeads (particle size 5-8 microns) and 70% of flexible acrylic resin;

[0078] Step 6: Evenly spread the mixed resin on the surface of the polycarbonate substrate;

[0079] Step 7: Pre-curing the substrate covered with resin at a curing temperature of 25°C for 1.5 hours;

[0080] Step 8: Use a roller with a pattern to press out an uneven pattern on the surface of the pre-cured substrate;

[0081] Step 9: Place the embossed substrate at 80°C for 1 hour to cure the resin completely;

[0082] Step 10: After the resin is cured, the molding and processing of the material are completed. The thickness of the basic transparent luminous layer and the anti-slip and wear-resistant layer are 25 mm and 50 μm respectively.

[0083] Example 3

[0084] The steps for composite material molding are as follows:

[0085] Step 1: drying the transparent polycarbonate raw material at 110° C. for more than 4 hours to obtain dried polycarbonate plastic particles;

[0086] Step 2: uniformly mixing 2% of the mass of the dried polycarbonate plastic particles with azodicarbonamide;

[0087] Step 3: Add the mixed raw materials into the barrel of the injection molding machine / extruder, and set the barrel temperature to 80°C;

[0088] Step 4: Set the molding temperature to 280°C, injection / extrude the polycarbonate sheet, and the porosity is about 12%;

[0089] Step 5: Evenly mix 40% by mass of transparent alumina microbeads (particle size 3-5 microns) and 60% of flexible modified epoxy resin;

[0090] Step 6: Evenly spread the mixed resin on the surface of the polycarbonate substrate;

[0091] Step 7: Pre-curing the substrate covered with resin at a curing temperature of 25°C for 2 hours;

[0092] Step 8: Use a roller with a pattern to press out an uneven pattern on the surface of the pre-cured substrate;

[0093] Step 9: Place the embossed substrate at 60°C for 4 hours to cure the resin completely;

[0094] Step 10: After the resin is cured, the molding and processing of the material are completed. The thickness of the basic transparent luminous layer and the anti-slip and wear-resistant layer are 15 mm and 50 μm respectively.

[0095] Example 4

[0096] The steps for composite material molding are as follows:

[0097] Step 1: drying the transparent polycarbonate raw material at 110° C. for more than 4 hours to obtain dried polycarbonate plastic particles;

[0098] Step 2: uniformly mixing azodicarbonamide accounting for 5% of the mass of the dried polycarbonate plastic particles with the dried polycarbonate plastic particles;

[0099] Step 3: Add the mixed raw materials into the barrel of the injection molding machine / extruder, and set the barrel temperature to 80°C;

[0100] Step 4: Set the molding temperature to 280°C, injection / extrude the polycarbonate sheet, and the porosity is 30%;

[0101] Step 5: Evenly mix 50% by mass of transparent alumina microbeads (particle size 10-15 microns) and 50% of flexible modified epoxy resin;

[0102] Step 6: Evenly spread the mixed resin on the surface of the polycarbonate substrate;

[0103] Step 7: Pre-curing the substrate covered with resin at a curing temperature of 25°C for 1.5 hours;

[0104] Step 8: Use a roller with a pattern to press out an uneven pattern on the surface of the pre-cured substrate;

[0105] Step 9: Place the embossed substrate at 80°C for 2 hours to cure the resin completely;

[0106] Step 10: After the resin is cured, the molding and processing of the material are completed. The thickness of the basic transparent luminous layer and the anti-slip and wear-resistant layer are 25 mm and 50 μm respectively.

[0107] Comparative Example 1

[0108] Step 1: drying the transparent polycarbonate raw material at 110° C. for more than 4 hours to obtain dried polycarbonate plastic particles;

[0109] Step 2: Evenly mix the dried polycarbonate plastic particles with sodium bicarbonate accounting for 10% of the mass of the dried polycarbonate plastic particles;

[0110] Step 3: Add the mixed raw materials into the barrel of the injection molding machine / extruder, and set the barrel temperature to 80°C;

[0111] Step 4: Set the molding temperature to 270°C, injection mold / extrude the polycarbonate sheet, and the porosity of the sheet after high-temperature discharge is about 10% (large through bubbles appear, and when cooled to room temperature, the bubbles shrink, causing the sheet to twist and deform).

[0112] Comparative Example 2

[0113] Step 1: drying the transparent polycarbonate raw material at 110° C. for more than 4 hours to obtain dried polycarbonate plastic particles;

[0114] Step 2: uniformly mix a mixture of triazole and azodicarbonamide accounting for 5% of the mass of the dried polycarbonate plastic particles with the dried polycarbonate plastic particles; wherein the mass ratio of triazole to azodicarbonamide is 4:6.

[0115] Step 3: Add the mixed raw materials into the barrel of the injection molding machine / extruder, and set the barrel temperature to 80°C;

[0116] Step 4: Set the molding temperature to 270°C, injection / extrude the polycarbonate sheet, and the porosity of the sheet after high-temperature discharge is about 30%;

[0117] Step 5: Mix the ordinary epoxy resin evenly;

[0118] Step 6: Evenly spread the mixed resin on the surface of the polycarbonate substrate;

[0119] Step 7: Pre-curing the substrate covered with resin at a curing temperature of 25°C for 1.5 hours;

[0120] Step 8: Use a roller with a pattern to press out an uneven pattern on the surface of the pre-cured substrate;

[0121] Step 9: Place the embossed substrate at 80°C for 2 hours to cure the resin completely;

[0122] Step 10: After the resin solidifies and returns to room temperature, tiny cracks appear on the resin wear-resistant layer on the surface of the board.

[0123] Test experiment

[0124] The process methods in the embodiments and comparative examples are adopted to obtain products, respectively, and the products are tested for compression resistance, weather resistance, multi-angle luminescence, bonding strength, impact resistance, etc.

[0125] Stress resistance:

[0126] Refer to GB / T 24725 "Raised road signs" for compressive load test;

[0127] Shock resistance:

[0128] Refer to GB / T 24725 "Raised road signs" for impact resistance test;

[0129] Wear-resistant:

[0130] Refer to Appendix B of GB / T 24725 "Raised Road Signs" - Test Method for Wear Resistance of Raised Road Signs, and use the vertical falling sand method to evaluate the wear resistance of the material surface;

[0131] Anti-slip:

[0132] Refer to GB / T 24717-2009 "Preformed Road Marking Strips" and use a pendulum friction coefficient tester for measurement;

[0133] Bonding: Refer to GB / T 7124 "Determination of tensile shear strength of adhesives"

[0134] The basic transparent luminous layer is made into a standard test plate according to the size requirements, and the anti-slip and wear-resistant layer is used as the bonding layer. The universal tensile testing machine is used for testing;

[0135] Lighting Angle:

[0136] Refer to SJ / T 11281 "Light Emitting Diode (LED) Display Screen Test Method" to test the light viewing angle

[0137] Light transmittance: Refer to GB / T 2410 "Determination of light transmittance and haze of transparent plastics"

[0138] The transmittance is calculated as follows:

[0139] T t =T2 / T1*100

[0140] Tt represents the transmittance, T2 represents the total transmitted light flux through the sample, and T1 represents the incident light flux;

[0141] Weather resistance: Refer to GB / T 14522 "Artificial climate accelerated test methods for plastics, coatings and rubber materials for mechanical industrial products" Appendix C Exposure cycle type 1 for testing; the detailed test conditions are as follows: UVA340 fluorescent UV lamp is selected, the exposure cycle is 8 hours of drying and 4 hours of condensation, and the irradiance is 0.89±0.02W / (m 2 *nm), blackboard temperature 50±3℃, test time 1000h.

[0142] Table 1

[0143]

[0144]

[0145] It can be seen from the table that various test indicators of the present invention can meet the standard requirements.

[0146] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0147] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A transparent composite material for displaying luminescence, characterized in that: The transparent composite material comprises a basic transparent luminescent layer and an anti-skid and wear-resistant layer; the raw materials of the basic transparent luminescent layer comprise polycarbonate and azo, hydrazine or azole compounds, and the raw materials of the anti-skid and wear-resistant layer comprise aluminum oxide and resin.

2. The transparent composite material for displaying luminescence according to claim 1, characterized in that: The mass ratio of the polycarbonate to the azo, hydrazine or azole compound is 100:(1-5).

3. The transparent composite material for displaying luminescence according to claim 1, characterized in that: The azo, hydrazine or azole compound is selected from one or more of triazole, azobisisobutyronitrile, azodicarbonamide, benzenesulfonylhydrazide and p-toluenesulfonylhydrazide.

4. The transparent composite material for displaying luminescence according to claim 1, characterized in that: The porosity of the basic transparent light-emitting layer is 10% to 50%.

5. The transparent composite material for displaying luminescence according to claim 1, characterized in that: Also includes any one or more of the following features: A1) the mass ratio of the aluminum oxide to the resin is (10-50): (50-90); A2) the resin is a modified epoxy resin or acrylic resin; preferably, the modified epoxy resin or acrylic resin is grafted with silicone or polyurethane functional groups; A3) the aluminum oxide is transparent aluminum oxide microbeads; A4) The particle size of the aluminum oxide is 2 to 20 microns.

6. The transparent composite material for displaying luminescence according to claim 1, characterized in that: Also includes any one or more of the following features: B1) the thickness ratio of the basic transparent luminous layer to the anti-slip and wear-resistant layer is 100:0.1-0.4; B2) the thickness of the anti-slip and wear-resistant layer is 20 to 200 microns; B3) the contact surface between the basic transparent luminous layer and the anti-slip and wear-resistant layer is a frosted or serrated structure; B4) A surface of the anti-slip and wear-resistant layer away from the basic transparent luminous layer is frosted or serrated.

7. The method for preparing a transparent composite material for displaying luminescence according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: 1) Mixing polycarbonate with azo, hydrazine or azole compounds and then injecting or extruding to obtain a polycarbonate sheet or three-dimensional structure; 2) uniformly mixing the aluminum oxide and the resin to obtain a mixed resin composite; 3) The mixed resin composite obtained in step 2) is laid flat on the surface of the polycarbonate sheet plate or three-dimensional structure obtained in step 1) for pre-curing and curing to obtain a transparent composite material for displaying luminescence.

8. The method for preparing a transparent composite material for displaying luminescence according to claim 7, characterized in that: Also includes any one or more of the following features: C1) In step 1), the polycarbonate needs to be dried first to obtain a dried polycarbonate, and the dried polycarbonate is mixed with an azo, hydrazine or azole compound; C2) in step 1), the injection molding or extrusion is carried out in an injection molding machine or an extruder barrel; C3) In step 1), the molding temperature is 260°C to 310°C; C4) in step 3), the pre-curing temperature is 20°C to 80°C; C5) in step 3), the pre-curing time is 0.1 to 2 hours; C6) In step 3), the curing temperature is 30°C to 80°C; C7) In step 3), the curing time is 1 to 6 hours; C8) In step 3), during the pre-curing, the shaping can be assisted by a frosted or serrated structure fixture; C9) In step 3), after the pre-curing, a frosted or serrated structure may be pressed out and then cured.

9. The method for preparing a transparent composite material for displaying luminescence according to claim 8, characterized in that: Also includes any one or more of the following features: C11) In step 1), the drying temperature is 100-120°C; C12) In step 1), the drying time is more than 4 hours.

10. Use of the transparent composite material for displaying luminescence according to any one of claims 1 to 6 and / or the transparent composite material for displaying luminescence prepared by the preparation method according to any one of claims 7 to 9 in the field of road traffic pavement display.